Challenges in the implementation of BIM: Quantity Surveyors perspective / Mohamad Amir Asyraf Kamal Mihad and Syed Abdul Haris Syed Mustapa - Kamal Mihad, Mohamad Amir Asyraf; Syed Mustapa, Syed Abdul Haris (2020)
Building Information Modelling (BIM) is not a new thing in the Architecture, Engineering and Construction (AEC) industry. It has been long introduced and being applied. Slowly but surely it is replacing the old traditional way of work in the construction industry. However, even though BIM had already been introduced in Malaysia construction industry for some time, the implementation is quite slow. The same goes among Quantity Surveyors. Somehow Quantity Surveyors still using traditional method throughout their works. This is a loss as there are already many studies exploring the advantages of BIM for Quantity Surveyors when compared to traditional method that Quantity Surveyors has been using all along. This study has been conducted among Quantity Surveyors in Perak. The aim of the research is to identify the best solution to the challenges in implementing BIM for Quantity Surveyors. The objectives of this research are i) To identify the challenges in the implementation of BIM for quantity surveyors ii) To investigate the method to overcome these challenges. The findings show that the biggest challenge for Quantity Surveyor to implement BIM is the high cost needed. The cost includes the installation of hardware and software and even the price of personnel training. The challenge in implementing BIM as syllabus for Quantity Surveying course is due to the lack of skilled personnel. The best solution extracted from the study is by providing funds for universities for them to implement BIM as a syllabus. This could help in implementing BIM as a syllabus while at the same time increasing the number of skilled personnel in BIM after the students graduated.